2001
DOI: 10.1097/00042728-200102000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Postoperative Drainage with 20% Ferric Chloride After Chemical Matricectomy with Phenol

Abstract: Phenol used in partial matricectomy shows its effects by denaturing matrix proteins. This highly successful method has the major problem of oozing which can continue for 5-6 weeks. objective. The goal of this study was to determine the effect of 20% ferric chloride (FC) (FeCl 3 ) on minimizing the oozing after chemical matricectomy with phenol. methods. Sixty-seven patients with stage III onychocryptosis were treated by chemical matricectomy with 90% aqueous phenol. In 32 of these patients FC was applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…9 A 20% ferric chloride solution can be used just after phenolization to improve postoperative drainage. 10 Slight edema in the lateral and proximal nail folds may remain for 1 week, and can be improved by applying clobetasol cream. Infection, although rare, is the most common complication.…”
Section: Management Of Complicationsmentioning
confidence: 99%
“…9 A 20% ferric chloride solution can be used just after phenolization to improve postoperative drainage. 10 Slight edema in the lateral and proximal nail folds may remain for 1 week, and can be improved by applying clobetasol cream. Infection, although rare, is the most common complication.…”
Section: Management Of Complicationsmentioning
confidence: 99%
“…The recurrence rate after phenol ablation is reported to be 5%. Complications included soft tissue necrosis, corrosion, drainage lasting >6 weeks, and rare systemic toxicity (22,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Complications, such as spicule formation, infection, tissue necrosis, pain, exudative fluid leakage, and periostitis, have been reported in association with phenol matricectomy [7,20,21]. Aksakal et al [21] reported a significant reduction in the exudative fluid leakage with the application of 20% ferric chloride followed by phenolization. The lack of spicule formation in all patients in the current study indicates that the technique is particularly important.…”
Section: Discussionmentioning
confidence: 99%